Omega‐3 fatty acids increase the unfolded protein response and improve amyloid‐β phagocytosis by macrophages of patients with mild cognitive impairment. Issue 10 (19th September 2017) - Olivera‐Perez, Henry M.; Lam, Larry; Dang, Johnny; Jiang, Weilan; Rodriguez, Fabian; Rigali, Elizabeth; Weitzman, Sarah; Porter, Verna; Rubbi, Liudmilla; Morselli, Marco; Pellegrini, Matteo; Fiala, Milan
ABSTRACT: Macrophages (Mϕs) of patients with Alzheimer's disease and mild cognitive impairment (MCI) are defective in amyloid‐β1‐42 (Aβ) phagocytosis and have low resistance to apoptosis by Aβ. Omega‐3 fatty acids (ω‐3s) in vitro and in vivo and the ω‐3 mediator, resolvin D1, in vitro increase Aβ phagocytosis by Mϕs of patients with MCI. We have investigated the unfolded protein response (UPR) to endoplasmic reticulum (ER) stress by Mϕs in a longitudinal study of fish‐derived, ω‐3–supplemented patients with MCI. Patients in the apolipoprotein E (ApoE) e3/e3 subgroup over time exhibited an increase of protein kinase RNA‐like ER kinase (PERK) expression, Aβ phagocytosis, intermediate M1‐M2 Mϕ type, and a Mini‐Mental State Examination (MMSE) rate of change of +1.8 points per year, whereas patients in the ApoEe3/e4 subgroup showed individually divergent results with an MMSE rate of change of –3.2 points per year. In vitro treatment of Mϕs by fish‐derived ω‐3 emulsion increased Aβ phagocytosis, PERK expression, and UPR RNA signature, and decreased ER stress signature. Augmented genes in the UPR signature included chaperones, lectins, foldases, and N‐linked glycosylation enzymes. In summary, fish‐derived ω‐3s increase cytoprotective genes and decrease proapoptotic genes, improve immune clearance of Aβ, and are associated with an improved MMSE rate of change in ApoEe3/e3 vs . ApoEe3/e4 patients.—Olivera‐Perez, H. M., Lam, L., Dang, J., Jiang, W., Rodriguez, F., Rigali, E., Weitzman, S., Porter, V., Rubbi, L., Morselli, M., Pellegrini, M., Fiala, M. Omega‐3 fatty acids increase the unfolded protein response and improve amyloid‐β phagocytosis by macrophages of patients with mild cognitive impairment. FASEB J. 31, 4359–4369 (2017). www.fasebj.org